2018
DOI: 10.1097/pts.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Using System Inflammatory Response Syndrome as an Easy-to-Implement, Sustainable, and Automated Tool for All-Cause Deterioration Among Medical Inpatients

Abstract: Whereas the definition of sepsis moves away from SIRS, SIRS-based criteria may still have clinical benefit as an easy-to-automate detection tool for all-cause clinical deterioration among medical inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…Six studies adopted models already developed and available in the literature 25 28 32 35 38 39. The remaining seven studies selected items using a combination of literature and clinical judgement27 34 37 or did not describe the method for selecting alert thresholds 36 40–42…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies adopted models already developed and available in the literature 25 28 32 35 38 39. The remaining seven studies selected items using a combination of literature and clinical judgement27 34 37 or did not describe the method for selecting alert thresholds 36 40–42…”
Section: Resultsmentioning
confidence: 99%
“…Studies described their systems as: a Modified Early Warning Score (MEWS);38 39 41 the EWS;34 the National Early Warning Score (NEWS);35 a combination of the NEWS, the Chronic Respiratory EWS and a palliative care tool;28 the Central Manchester University National Health Service Foundation Trust EWS;42 and the Rothman Index 25. One study used the systemic inflammatory response syndrome criteria 40. A multisite study used a variety of EWS across various sites,36 while five studies reported customising an existing EWS for their institutions 27 31 32 34 37.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations